The Relationship between Balance, Agility, and Eye-Foot Coordination to Dribbling Ability in the Football Game of the Tancung Putra Team of Wajo Regency - Hasbillah, Muhammad; Suparman, Suparman; Herman, Herman; Nurafiati, Suastika; Asri, Ariana; Angriawan, Tri (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This study aims to determine the relationship between balance, agility and eye-foot coordination on dribbling ability in football games. The sample in this study was the Tancung Putra Wajo Regency team, totalling 30 people with a saturated sampling technique. The data analysis technique used is the correlation coefficient. The research results show a significant relationship between balance and the ability to dribble in a football game, with a value of r = 0,747. There is a substantial relationship between agility and the ability to dribble in a football game with a value of r = 0,766, there is a significant relationship between eye-foot coordination and the ability to dribble in a football game with a value of r = 0,702, and there is a substantial relationship of balance, agility and eye-foot coordination together on the ability to dribble in a football game with a value of R = 0,825.